THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND PECEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL COMMITMENT: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT - SYADINA, KHANSA PUTRI; PURNOMO, RATNO; ANGGRAENI, ADE IRMA (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
This study aims to determine the influence of transfromational leadership, perceivedorganizational support, and employee engagement of organizational commitment. Thesurvey was conducted at Inspectorate Bekasi. There were 57 respondents selected throughpurposive sampling method. Respondents are permanent employees in the organizationand work for a minimum of five years. Based on the results of research by using multipleregression, and causal step mediation method, it can be conclude : (1) transformationalleadership has a positive affects to employee engagement, (2) perceived organizationalsupport has no positive affects to employee engagement, (3) transformational leadershiphas a positive affects to organizational commitment, (4) perceived organizationalcommitment has a positive affects to organizational commitment, (5) employee engagementhas a positive affects to organizational commitment, (6) employee engagement mediatesthe relationship between transformational leadership towards organizational commitment,and (7) employee engagement doesn?t mediates the relationship between perceivedorganizational support towards organizational commitment. The implication of this researchis if an organization has employees who instill a sense of employee engagement whoalways proud, enthusiasm of their work, and time feels fast at work will greatly affectorganizational commitment. Then, if having a transformational leader that directs themission to the organization, has a purpose, and expressed a sense of satisfaction inemployees will be able to increase the sense of employee engagement and organizationalcommitment. In addition, organizations that concerning of employees welfare, pride inemployees achievement, and appreciate the contribution of employees can also increaseorganizational commitment in Inspectorate Bekasi